PEMANFAATAN DAN PENGUJIAN APLIKASI VARNISH WEB CACHE UNTUK MEMPERCEPAT AKSES WEBSITE - Kusumo, Eko Bayu; Andjarwirawan, Justinus; Gunawan, Ibnu (Jurnal Infra, 2014)
Website technology is currently growing very rapidly. A Website started to be equipped with a variety of animations to make it more interesting but sometimes the animation slowing access of a Website. People will leave the Website because of loading time taking too long. One way to speed up a Website access is by utilizing web applications using Varnish cache. Varnish will store static data from a Website in the memory. Static data is data that changes infrequently or rarely updated.A front end for Web administrators will be built for Varnish application so that the configuration can be easily replaced as needed. The configuration will be simplified through the front end of this Varnish application is detecting SQL injection and Cross Site Scripting (XSS), block files dan folders, HTTP header manipulation, detects the original file is deleted or blocked and error handling configuration. Application front end is implemented in a virtual machine with VirtualBox as its virtual manager and Linux Ubuntu server as its virtual operating system.Varnish application was tested using ApacheBench where the number of requests from the client and the response time becomes the main parameters of the test.